Four Traumatic Asphyxial Cases with an "Masque Ecchymotique" in Pediatric Emergency Department - Oksan Derinöz Güleryüz; Taner Akar; Yasemin Men Atmaca (Galenos Yayinevi, 2020)
Traumatic asphyxia is a rare and serious clinical syndrome, which is identified by subconjunctival haemorrhage, facial oedema, craniocervical cyanosis and petechiae on the upper chest and the face regions. It occurs when the chest and/or upper abdomen regions are subjected to blunt trauma due to sudden compressions. This syndrome may develop if there is an occurrence of Valsalva manoeuvre during thoracic compression. Although patients appear to be very clinically ill, they can still have a very good prognosis with effective and timely treatment. However, long-term thoracic compressions may cause cerebral anoxia and neurological sequelae. Its treatment is usually conservative, and the course depends on the accompanying injuries. Herein, we report four cases of traumatic asphyxia that can be recognised by the physicians working in the paediatric emergency department if they are aware of the diagnosis.